Study on collocational competence of Malay students in their English speaking proficiency - Abdullah, Arifuddin; Abdul Ghani, Rozina (IIUM Press, International Islamic University Malaysia, 2017)
This book aims to investigate the students’ collocational competence by examining the relationship between the knowledge of lexical collocation and their speaking proficiency as well as to identify the patterns of collocational mis(use) among them. The respondents involved comprised 30 students of Universiti Malaysia Kelantan (UMK). A lexical collocation test (LCT) was constructed to gauge the knowledge of collocation, while a speaking proficiency test (SPT) adopted from the IELTS was administered to determine the students’ level of speaking proficiency. Both variables were then correlated. The result indicated that there is no significant correlation between the knowledge of collocation and speaking proficiency among the respondents. This study also revealed that the majority of the respondents did not perform well in LCT. On the patterns of errors made, the scores on LCT revealed that the respondents struggled with the Noun 1 + of + Noun 2 and Verb + Adverb categories. However they performed well in the Verb + Noun and Adjective + Noun categories. Besides, the data from the speaking proficiency test pointed out that miscollocation mostly occurred in the Verb + Noun and Adjective + Noun categories. Based on the findings, it was revealed that exposure to the target language plays a vital role in language acquisition. Exposure to collocations in particular will enable the learners to speak more fluently and sound more native-like. This book comprises five chapters. Chapter One covers the introduction presenting the background of the research including the historical background of the subject matter, the statement of the problem, the significance of the study, the objectives of the study and the research questions. Chapter Two presents a review of the literature of related studies in the field as well as the theoretical framework underpinning this study. Chapter Three describes the methodology used and presents a thorough explanation of the research design, respondents, data collection method, instruments and data analysis. Chapter Four discusses the findings of the study. The final chapter concludes and offers a detailed discussion on pedagogical implications, based on the research findings.